Balance assessment after altering stimulation of the neurosensory system - Valentina Li Causi; Alessandro Manelli; Valentina Gianpaola Marini; Mario Cherubino; Luigi Meccariello; Michael Mazzacane; Mario Ronga (Medicinski glasnik, 2020)
Aim: Posture requires fine integrative elaboration, performed by the central nervous system, of neurosensory information originated from the visual, vestibular and spinal circuit. Many perturbing agents can influence this elaboration and then the postural stability. Several studies have evaluated only the effect of a single agent on the postural control. The study analysed the perturbing effect of several external agents on the different sensorial circuits in terms of postural balance loss in orthostatism. Methods: The postural stability of 31 patients was evaluated with a static posturography platform in basal conditions and after exposure to an external agent in the following order: stroboscopic light projecting, mechanical rotations on a swivel chair, feet desensitization through ice, administration of an alcoholic drink at intervals which depended on the participant return to basic posturographic values. Tests were performed with open eyes (OE), closed eyes (CE) and reducing plantar perception through the use of a rubber pillow. Results: The stroboscopic light altered the postural control. The swivel chair disturbed only with CE. Ice and alcohol increased the oscillation area. The alcohol test had a significant reduction in postural control with OE compared to CE. The rubber cushion increased the oscillation area in all OE tests and with CE in alcohol and ice tests. Conclusion: The different agents did not trigger postural control deficits in the same way. A cold environment with psychedelic lights and the use of alcoholic beverages altered significantly the postural stability by influencing simultaneously all perceptions (visual, vestibular and somatosensory feedback).
Keywords: central nervous system; postural balance; sensation disorders; vestibular; visual perception